Implemention scheme of IP short message for VoLTE users - Xiao JING (物联网学报)
The traditional circuit domain short message service is provided by SMSC (short message service center),and the business processes are carried in the seven signaling network.With the commercial use of IMS network,it is necessary for operators to continue to provide short message service for VoLTE users in the IP network,which is the function that operators must support in the process of network evolution.The IP-SM-GW functions,processes,system architecture,interface solutions and other issues are introduced,and IP-SM-GW into the current network is put forword.